Garfield the movie - Cohen, Joel; Davis, John; Lawrence, Mark Christopher 1964-; Davis Entertainment Company; Twentieth Century-Fox Film Corporation ([United States] 20th Century Fox Home Entertainment, 2006)
Garfield's owner, Jon, takes in sweet, but dimwitted pooch Odie, turning Garfield's perfect world upside-down. Now Garfield wants only one thing: Odie out of his home and his life! But when the hapless pup disappears and is kidnapped by a nasty dog trainer, Garfield, feeling responsible, tears himself away from the TV and springs into action
Based on the comic strip characters created by Jim Davis
Title from container
1 2
Keywords: Children's films; Comedy; Garfield (Fictitious character) -- Drama; Human-animal relationships -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs